Delimitation of Ophioderma teres (Lyman, 1860) and Ophioderma unicolor H.L. Clark, 1940 stat. nov. (Echinodermata: Ophiuroidea), including the description of two new species - Karla J. Humara-Gil; Rebeca Granja-Fernández; Eric Bautista-Guerrero; Francisco A. Solís-Marín; Alma P. Rodríguez-Troncoso (European Journal of Taxonomy, 2024)
Ophioderma teres (Lyman, 1860), an ophiuroid previously believed to have a wide distribution in the eastern Pacific, has been found to have an unclear taxonomic identity. While considered a well-known species, recent studies have revealed that O. teres lacks a holotype and has vague boundaries with its congeners Ophioderma teres unicolor H.L. Clark, 1940 and Ophioderma sodipallaresi Caso, 1986, as well as with two additional new morphotypes detected in Mexico and Nicaragua, causing continuous misidentifications. This study utilized an integrative taxonomy approach based on morphologic, morphometric, and molecular evidence to clarify the taxonomic status of O. teres, O. sodipallaresi, O. teres unicolor, and the two new morphotypes. Data integration led to the following results: 1) the neotype designation and redescription of O. teres; 2) the proposal of O. sodipallaresi as a junior synonym of O. teres; 3) the status change of O. unicolor stat. nov. from subspecies to species, and 4) the description of the morphotypes as the new species Ophioderma aija sp. nov. and Ophioderma bichi sp. nov. An identification key to the eastern Pacific species of Ophioderma was also developed. This work contributes to the knowledge of Ophioderma in the region, increasing the number of described species and providing resources for their accurate identification.